2014
DOI: 10.1001/jamainternmed.2014.3033
|View full text |Cite
|
Sign up to set email alerts
|

Morning Handover of On-Call Issues

Abstract: IMPORTANCE Handover is the process of transferring pertinent patient information and clinical responsibility between health care practitioners. Few studies have examined morning handover from the overnight trainee to the daytime team.OBJECTIVE To characterize current morning handover practices in 2 academic medical centers by assessing the frequency of omissions of clinically important overnight issues during morning handover and identifying factors that influence the occurrence of such omissions. DESIGN, SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Omissions of clinically important on-call issues by fatigued on-call residents when transferring care to the daytime team at the end of shifts are major contributors to miscommunications and can result in care implementation delays and adverse events [16]. Insuicient handof communication result in incomplete, inaccurate, and omited data and efectuate informational ambiguities between the departing and oncoming providers.…”
Section: Insuicient Handofs Induce Complicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Omissions of clinically important on-call issues by fatigued on-call residents when transferring care to the daytime team at the end of shifts are major contributors to miscommunications and can result in care implementation delays and adverse events [16]. Insuicient handof communication result in incomplete, inaccurate, and omited data and efectuate informational ambiguities between the departing and oncoming providers.…”
Section: Insuicient Handofs Induce Complicationsmentioning
confidence: 99%
“…Research by Devlin et al demonstrated that only 14% of clinically important issues from the overnight clinical shifts had an accompanying progress note from the on-call trainee in the patient's medical record [16]. Discontinuity of care secondary to inefectual handofs has been correlated with longer hospital stays and increased costs [3].…”
Section: Insuicient Handofs Induce Complicationsmentioning
confidence: 99%
See 3 more Smart Citations